Analisis Literasi Numerasi Matematis Siswa SMP - Azmy, Intan; Sumliyah, Sumliyah; Rahmatudin, Jajang (Universitas Muria Kudus, 2024)
Numeracy literacy is a significant ability in the modern era, especially in the context of education. This study aims to analyze and determine the mathematical numeracy literacy possessed by students in answering test questions related to the Pythagorean Theorem at the junior high school level. This research uses a qualitative approach with a descriptive method. The technique used in collecting research data uses an essay test consisting of 6 items related to the Pythagorean Theorem material. The participants in this study were ninth-grade students of class 9F at SMP Negeri 2 Plumbon, totaling 32 students. The data analysis of this study includes data reduction, data presentation, and conclusion drawing. Based on the research results, 9 students were in the high category with a percentage of 28%, 18 students were in the medium category with a percentage of 56%, and 5 students were in the low category with a percentage of 16%. Then the overall results of students' mathematical numeracy literacy from the test instrument test obtained 16 students out of 32 students with a percentage of 50% who have reached the Learning Achievement Criteria . Thus, it can be concluded based on the research results that the mathematical numeracy literacy of ninth-grade students of class 9F at SMP Negeri 2 Plumbon in answering test questions on the Pythagorean Theorem material is in the medium category and only 50% of students have reached the Learning Achievement Criteria